Why I am a Buddhist : No-Nonsense Buddhism with Red Meat and Whiskey - Asma, Stephen T. (Charlottesville, VA : Hampton Roads Pub. Co., 2009)
Profound and amusing, this book provides a viable approach to answering the perennial questions: Who am I? Why am I here? How can I live a meaningful life? For Asma, the answers are to be found in Buddhism. There have been a lot of books that have made the case for Buddhism. What makes this book fresh and exciting is Asmas iconoclasm, irreverence, and hardheaded approach to the subject. He is distressed that much of what passes for Buddhism is really little more than New Age mush. He loudly asserts that it is time to take the California out of Buddhism. He presents a spiritual practice that does not require a belief in creeds or dogma. It is a practice that is psychologically sound, intellectually credible, and esthetically appealing. It is a practice that does not require a diet of brown rice, burning incense, and putting both your mind and your culture in deep storage. In seven chapters, Asma builds the case for a spiritual practice that is authentic, and inclusive. This is Buddhism for everyone. This is Buddhism for people who are uncomfortable with religion but yearn for a spiritual practice.
Keywords: Buddhism -- Apologetic works